VALIDITY AND PRACTICALITY OF FLASH CARD PUZZLE AS A LEARNING MEDIA IN EARTH LAYERS CLASS VII - Nisak Ummi Nazikhah; Af'idah, Noer (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2023)
The role of learning media was important to helped students for understood learning proccesed. The selection of learning media was concerned about the suitability of students and the material being studied. The earth layers materials in science lesson was materials that needed a learning media. For this reason, researchers developed a flash card puzzle learning media. This study aims to produced flash card puzzle learning media on class VII SMP/MTs earth layer material that is valid and practical. This development used the ADDIE development model which had step of analize, design, development, implementation, and evaluation. The validity test was conducted by media assessment by validator, they were media expert, material expert, and science teachers. The practicality test was carried out by assessing the activities of teachers (researchers) when was using the media, assessing the activities of students when was using the media, and filling out questionnaires of student responses about satisfaction after used flash card puzzle media. The results of the validity test and practicality test of flash card puzzle media obtained an average score of 3.44 with very valid criteria and 87% with very practical criteria. Based on these data, the development of flash card puzzle media learning media was valid and practical to be used in the learning process of class VII earth layer material.